Attractive Human Face as a Communication Tool: Age and Gender Specifics of the Attractiveness of Sexually Dimorphic Features in Facial Composites - Démuthová, Slávka; Hudáková, Alexandra (Communication Today, 2024)
An attractive human face is a significant communication tool used in visual media. Due to various psychological mechanisms, a beautiful face is associated with additional characteristics; individuals with attractive faces are perceived as trustworthy, intelligent, and qualified, thereby increasing their impact on the perceiver. However, the question remains as to what constitutes an attractive human face and what parameters it should possess. One of the most influential characteristics associated with facial attractiveness is the presence of sexually dimorphic features. Since previous research has yielded conflicting findings, this study examines the influence of masculinity and femininity on the attractiveness of computer-generated facial composites, both generally and in the context of the age and gender of the evaluators, using a quasi-experimental approach. The study involved 2,159 participants (mean age = 24.18 years; SD = 10.167), with women comprising 59.6% of the sample. The results showed that while the femininity of facial features universally increases the attractiveness of female faces (most notably among younger men), the effect of sexually dimorphic features on the attractiveness of male faces is nonspecific. Therefore, for the universal utilisation of the attractive face effect on the evaluator (perceiver), it is recommended to employ a feminine female face. In the case of male faces, the attractiveness of masculine features may be contingent on additional circumstances/factors.